2021
DOI: 10.1002/mnfr.202100443
|View full text |Cite
|
Sign up to set email alerts
|

PBK Model‐Based Prediction of Intestinal Microbial and Host Metabolism of Zearalenone and Consequences for its Estrogenicity

Abstract: The aim of the present study is to develop physiologically-based kinetic (PBK) models for rat and human that include intestinal microbial and hepatic metabolism of zearalenone (ZEN) in order to predict systemic concentrations of ZEN and to obtain insight in the contribution of metabolism by the intestinal microbiota to the overall metabolism of ZEN. Methods and Results: In vitro derived kinetic parameters, apparent maximum velocities (V max ) and Michaelis-Menten constants (K m ) for liver and intestinal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 71 publications
(134 reference statements)
0
19
0
Order By: Relevance
“…Previous studies showed a proof of the principle for the inclusion of gut microbial metabolism in PBK modeling using kinetic parameters derived from in vitro anaerobic fecal incubations. 25,26 The model predicted the C max of GA and PG, after consumption of two capsules of the EGCG supplement (the recommended daily intake), to be less than 1.5% of the blood C max of EGCG and less than 14.1% when expressed in unbound EGCG equivalents in plasma. The increase in the percentage is due to both the REP values for GA and PG that are higher than the REP value of 1.0 for EGCG and the fact that the plasma fraction unbound values of GA and PG are 1.8 and 4.5 times that of EGCG, respectively.…”
Section: ■ Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies showed a proof of the principle for the inclusion of gut microbial metabolism in PBK modeling using kinetic parameters derived from in vitro anaerobic fecal incubations. 25,26 The model predicted the C max of GA and PG, after consumption of two capsules of the EGCG supplement (the recommended daily intake), to be less than 1.5% of the blood C max of EGCG and less than 14.1% when expressed in unbound EGCG equivalents in plasma. The increase in the percentage is due to both the REP values for GA and PG that are higher than the REP value of 1.0 for EGCG and the fact that the plasma fraction unbound values of GA and PG are 1.8 and 4.5 times that of EGCG, respectively.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The conceptual PBK model of EGCG, including sub-models for GA and PG, for humans is presented in Figure . The model is modified from PBK models developed and evaluated previously for zearalenone and daidzein also taking gut microbial metabolism into account. , The model includes a separate compartment for liver as the biliary excretion and metabolizing compartment, and compartments for stomach, fat, kidney, blood, small intestinal lumen, small intestine tissue, large intestinal lumen, slowly perfused tissue (muscle, skin, and bone), and rapidly perfused tissue. The model includes a stomach emptying process, and the small intestinal lumen was divided into seven sub-compartments, enabling the description of the transition within the small intestine .…”
Section: Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations